Determination of Dipole Polarization Effects in 7Li and 11Li - Skouras, L. D.; Muther, H.; Nagarajan, M. A. (HNPS Advances in Nuclear Physics, 2019)
The structure of 6Li, 7Li and 11Li nuclei is investigated in a model space which includes all configurations with oscillator energy up to 3hω above the ground state configuration. The energy spectra and electromagnetic properties of the low-lying states are determined with various two-body interactions, which are derived from the Bonn potential. In addition the calculation determines the dipole polarizability of7 Li and 11Li caused from virtual E1 excitations to the positive parity states of these nuclei.